Analisis Peningkatan Minat Terhadap Produk Asuransi Syariah - Alexander Apryan Tamba; Muhammad Zacki Arafli; Dede Alvian; Andry Setiawan (Pusat Riset dan Inovasi Nasional, 2024)
Several key factors influence consumer interest in Islamic insurance: understanding of sharia principles, perceptions of how compatible Islamic insurance is with religious values, trust in Islamic insurance institutions, and positive reviews from other customers. In addition, factors such as education and socialization about Islamic insurance products, product innovation, promotion, service and customer satisfaction in accordance with consumer needs. The purpose of this research is to find methods that can increase customer interest in insurance. The research method involves a case study analysis of how insurance companies can increase customer interest. The findings show that factors such as education, proper promotion, and good customer service, play a significant role in increasing customer interest in insurance. This research suggests that insurance companies should implement these strategies to attract consumers and expand their market share.